(untitled) (International journal of artificial intelligence, 2026)
This article analyzes the role and significance of the rule of law in the process of establishing a legal state from a scientific, theoretical and practical perspective. The concept of the rule of law, its essence as a main feature of a legal state, its significance in society and state governance are highlighted. The theoretical and legal foundations and practical mechanisms of the process of establishing a legal state in the Republic of Uzbekistan are analyzed in depth. The scientific content of the concept of a legal state, its inextricable connection with constitutional principles and its role in the national legal system are revealed. The issues of legislative reforms aimed at forming a legal state in the country, modernization of the judicial and legal system, improvement of human rights protection mechanisms and development of civil society institutions are also analyzed.